Tingkat konsumsi garam beryodium dan kaitannya dengan gangguan akibat kekurangan yodium ibu hamil - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ABSTRACT Background: Iodine deficiency disorders (IDD) is one of main nutrition problems which cannot be eliminated until now in Indonesia. Total goiter rate (TGR) of school children increased from 9.8% in 1998 to 11.1% in 2003. In Gunung Kidul District, TGR of school was 12.2% and of pregnant mothers was 18.4% in 1996. One of efforts to overcome IDD is salt iodization. Result of a national survey of household iodized salt consumption in 2002 showed that only 68.53% of households consumed sufficient level of iodized salt, while salt monitoring at Gunung Kidul District in 2003 showed that only 73.08% of households consumed sufficient level of iodized salt. The low rate of consumption level of iodized salt may be caused by availability of salt with low iodine level (not as high as mentioned in the label), higher price of iodized salt and lack of knowledge about types and benefits of iodized salt among mothers. Objective: To identify consumption level of iodized salt and IDD status of pregnant mothers at IDD endemic area at Gunung Kidul District. Method: The study was an observational type which used cross sectional design with both quantitative and qualitative approaches. Subject of the study were pregnant mothers at their second trimester pregnancy. Results: Availability of iodized salt according to: quality was 81.1% low and 18.9% sufficient